Sensory characteristics and consumer preference for meat from guinea fowl fed hevea seed meal or cashew nut meal supplemented diets - G.A. Koné; M. Good; T. Tiho; Z.R. Ngatta; J.-F. Grongnet; M. Kouba (Poultry Science, 2022)
ABSTRACT: This study is part of a series of studies on the possibility of substituting alternative protein source supplements to the diet of guinea fowl in order to improve food security in the fight against poverty on the African Continent. This study assesses the identified sensory characteristics of guinea fowl meat and consumer preferences to determine if the possible alternative supplements identified result in a product acceptable to consumers and if consumer preference was evident. Indigenous guinea fowl or selected breed (Galor animals) were fed a control diet C, a commercial diet I (diet used for guinea fowl in Côte d'Ivoire), or one of 2 experimental diets N (diet C supplemented with 15% cashew nut meal) or diet H (diet C supplemented with 15% detoxified hevea seed meal). Meat samples were assessed by 120-trained people using 18 sensory attributes. Principal component analysis (PCA) showed that meats from guinea fowl fed diet C or diet I were clearly distinguished from guinea fowl fed N or H diets and that meat of indigenous guinea fowl or Galor animals were also clearly distinguished. The results of the hierarchical group analysis showed that meat from guinea fowl fed diet H was the preferred guinea fowl meat. A first partial least squares regression PLSR1 identified the relationships between guinea fowl meat samples, their sensory attributes and consumer preference and showed that 82.6% of the sensory data of the first 2 principal components accounted for 95.5% of the preference. The PLSR2 identified the relationships between guinea fowl samples, their sensory attributes, and their biochemical characteristics and showed that the fat content of the meat determined the intensity of flavor, odor, juiciness, and tenderness of the meat. Our results showed that meat from birds fed diet H was preferred, and thus emphasized the existence of a place for the use of hevea seed meal in guinea fowl diet in Côte d'Ivoire.